The time-varying propagation between oil market and stock market- An evidence of Pakistan Stock Exchange, PSX - Rehman, Atta Ur; Ullah, Hamid; Akram, Sabahat; Ghazanfar, Faheem; Khan, Muhammad Kamran; Ahmed, Masood; khan, Azhar (The journal of contemporary issues in business and government, 2021)
The prime objective of this study is to find out the time-varying propagation between the oil market and stock market. For this purpose the crudeoil future contracts in real time was chosen as proxy for an oil market determinant while two indices at Pakistan stock exchange were taken as stock market determinants. In this regard KSE100 index and KMI30 index (the Islamic index) were considered as stock market variables to examine short run or long run relationship amongst the oil market and stock market. The analysis was based on time series data. The weekly closing prices were collected for the period ranging from June, 2009 to August, 2020 with 583 total observations. The study used the Johanson and Juselius (1990) technique to examine the long run cointegration between the variables. The ADF test postulated that all series were at 1(0) nonstationary but it became stationary when taking it at 1st difference. The Johanson cointegration test examined that Pakistani stock indices were cointegrated in the long run with the crudeoil. Once Johanson test founded the long run relationship among the variable, VECM is used to examine the short run dynamics of long run equilibrium relationship. The variance decomposition revealed that fluctuations in the oil prices were strongly endogenous from its own variance in the short run but strongly exogenous in the long run from others independent variable in the model. The impulse response function demonstrated that response of KSE100 and KMI30 both to the shock of crudeoil showed increasing trend in the short run but in long run they have constantly decreasing trend.